2014
DOI: 10.1021/cm500825b
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conductive and Conformal Poly(3,4-ethylenedioxythiophene) (PEDOT) Thin Films via Oxidative Molecular Layer Deposition

Abstract: This work introduces oxidative molecular layer deposition (oMLD) as a chemical route to synthesize highly conductive and conformal poly­(3,4-ethylenedioxythiophene) (PEDOT) thin films via sequential vapor exposures of molybdenum­(V) chloride (MoCl5, oxidant) and ethylene dioxythiophene (EDOT, monomer) precursors. The growth temperature strongly affects PEDOT’s crystalline structure and electronic conductivity. Films deposited at ∼150 °C exhibit a highly textured crystalline structure, with {010} planes aligned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
141
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(150 citation statements)
references
References 35 publications
9
141
0
Order By: Relevance
“…300C shows no significant film growth (Figure S2). Atanasov et al reported oxidative polymerization in a molecular layer deposition process, indicating the possibility of such surface-controlled polymerization reactions 50. …”
mentioning
confidence: 99%
“…300C shows no significant film growth (Figure S2). Atanasov et al reported oxidative polymerization in a molecular layer deposition process, indicating the possibility of such surface-controlled polymerization reactions 50. …”
mentioning
confidence: 99%
“…Upon spin-coating from solution, the micelles are deposited as a film and can have conductivities on the order of ∼1 S/cm (22). Subsequent annealing, treatment with cosolvents, and postprocessing steps can increase the conductivity of films to over 3,000 S/cm (23,24). High-performing spin-cast PEDOT:PSS TCs have reached a sheet resistance of 46 Ω/□ at 90% transmission (25,26).…”
mentioning
confidence: 99%
“…The resulting oCVD CPs properties such as conductivity can be tuned by controlling the VOCl 3 and monomer flow rates as well as the substrate temperature. Molybdenum pentachloride (MoCl 5 ) is another solid oxidant demonstrated with oxidative molecular layer deposition (oMLD) . The oMLD method is a chemical extension of atomic and molecular layer deposition and introduces the oxidant and monomer vapors sequentially into a reactor chamber .…”
Section: Ocvd Synthesis Chemistrymentioning
confidence: 99%
“…Molybdenum pentachloride (MoCl 5 ) is another solid oxidant demonstrated with oxidative molecular layer deposition (oMLD) . The oMLD method is a chemical extension of atomic and molecular layer deposition and introduces the oxidant and monomer vapors sequentially into a reactor chamber . This is in contrast to the simultaneous delivery of the oxidant and monomer vapors for the oCVD method.…”
Section: Ocvd Synthesis Chemistrymentioning
confidence: 99%